Non-Alcoholic Fatty Liver Disease in HIV/HBV Patients – a Metabolic Imbalance Aggravated by Antiretroviral Therapy and Perpetuated by the Hepatokine/Adipokine Axis Breakdown - Iacob, Simona Alexandra; Iacob, Diana Gabriela (Frontiers in Endocrinology, 2022)
Non-alcoholic fatty liver disease (NAFLD) is strongly associated with the metabolic syndrome and is one of the most prevalent comorbidities in HIV and HBV infected patients. HIV plays an early and direct role in the development of metabolic syndrome by disrupting the mechanism of adipogenesis and synthesis of adipokines. Adipokines, molecules that regulate the lipid metabolism, also contribute to the progression of NAFLD either directly or via hepatic organokines (hepatokines). Most hepatokines play a direct role in lipid homeostasis and liver inflammation but their role in the evolution of NAFLD is not well defined. The role of HBV in the pathogenesis of NAFLD is controversial. HBV has been previously associated with a decreased level of triglycerides and with a protective role against the development of steatosis and metabolic syndrome. At the same time HBV displays a high fibrogenetic and oncogenetic potential. In the HIV/HBV co-infection, the metabolic changes are initiated by mitochondrial dysfunction as well as by the fatty overload of the liver, two interconnected mechanisms. The evolution of NAFLD is further perpetuated by the inflammatory response to these viral agents and by the variable toxicity of the antiretroviral therapy. The current article discusses the pathogenic changes and the contribution of the hepatokine/adipokine axis in the development of NAFLD as well as the implications of HIV and HBV infection in the breakdown of the hepatokine/adipokine axis and NAFLD progression.